2007
DOI: 10.1021/es062313l
|View full text |Cite
|
Sign up to set email alerts
|

Monod Kinetics for Aerobic Biodegradation of Petroleum Hydrocarbons in Unsaturated Soil Microcosms

Abstract: We use Monod kinetics to calibrate previously published data that documentthe aerobic biodegradation of hydrocarbon vapors in soil microcosms from a weathered petroleum spill site. Monod kinetics offer insight into biodegradation mechanics because they address biomass growth as well as substrate depletion. A blend of five aromatics and five alkanes dose the microcosm sets at four strengths, and a finite difference model describes the response superimposed across the constituent substrates. An observed initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…38 The yields of 0.21 g biomass g substrate −1 observed are in the range of values observed for other aromatic hydrocarbons. 38 Other Model Approaches.…”
Section: ■ Discussionmentioning
confidence: 52%
“…38 The yields of 0.21 g biomass g substrate −1 observed are in the range of values observed for other aromatic hydrocarbons. 38 Other Model Approaches.…”
Section: ■ Discussionmentioning
confidence: 52%
“…The maximum growth rate of P. aeruginosa with n-hexadecane and neicosane were 0.175 and 0.08 h À1 , respectively, while the corresponding growth rate with P. fluorescens were 0.1 and 0.16 h À1 , respectively. Ostendorf et al [25] observed the maximum growth rate of 0.09 d À1 with heneicosane using Acinetobacter, whereas Table 1 Comparison of microbial growth rate with degradation of paraffin and production of rhamnolipid at 40 h of incubation.…”
Section: Stability Of Rhamnolipidmentioning
confidence: 99%
“…Two types of model can be used for kinetic studies, namely, Monod and Logistic model. Many studies have been performed on the microbial growth and kinetics of degradation of hydrocarbons using the Monod growth model [18,25]. The Monod model involves the concept of growth limiting substrate.…”
Section: Introductionmentioning
confidence: 99%
“…This application is further enhanced by the published results of laboratory experiments that demonstrated a linear decrease in concentration of n-alkanes with the time of fuel incubation under aerobic conditions. The observed linear depletion of n-nonane and n-decane during hydrocarbon biodegradation in aerobic soil microcosms from a petroleum spill site was interpreted as indicating that microorganisms degrade the alkanes on a zero-order basis, whereas degradation of aromatic hydrocarbons follows first-order kinetics (Ostendorf et al, 2007). A broader range of n-alkanes was investigated in laboratory experiments on effects of aerobic biodegradation of North Sea crude oil on hydrogen isotopic composition of hydrocarbons (Pond et al, 2002).…”
Section: Biodegradation and Age-dating Of Middle Distillate Fuelsmentioning
confidence: 99%